Collateral and its Determinants: Evidence from Vietnam - Christa Hainz; Thanh Dinh; Stefanie Kleimeier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper analyses the determinants of collateral in loans granted to entrepreneurs and consumers. We use cross-sectional data on more than 39,000 bank loans raised by Vietnamese borrowers between 2006 and 2009. Our data set is unique because it contains information about the bank's assessment of the borrower's ex ante risk and the borrowers' wealth including pledged as well as unpledged assets. We find that observationally riskier borrowers, as measured by the bank through the ex ante risk score, are more likely to pledge collateral. At the same time, wealthier borrowers are more likely to pledge collateral in order to benefit from a reduction in their interest costs. We also present evidence on other determinants of collateral such as borrower-lender relationship, credit market competition, and institutions.
Keywords: G21; 330; Collateral; retail lending; observed risk hypothesis; loan pricing; emerging markets